2008
DOI: 10.1186/1471-2407-8-148
|View full text |Cite
|
Sign up to set email alerts
|

Modified FOLFOX-6 chemotherapy in advanced gastric cancer: Results of phase II study and comprehensive analysis of polymorphisms as a predictive and prognostic marker

Abstract: Background: The objective of this study was to evaluate the efficacy and toxicity of infusional 5-fluorouracil (5-FU), folinic acid and oxaliplatin (modified FOLFOX-6) in patients with advanced gastric cancer (AGC), as first-line palliative combination chemotherapy. We also analyzed the predictive or prognostic value of germline polymorphisms of candidate genes associated with 5-FU and oxaliplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 43 publications
3
55
3
1
Order By: Relevance
“…Several studies on TYMS expression and this polymorphism were reported especially in colorectal cancer, with some clinical studies showing favorable results in 2R/2R (32)(33)(34). However, two recent studies in advanced gastric cancer did not show any significant impact of this polymorphism as seen with our results (7,9). Although further studies may be necessary, the clinical significance of this polymorphism may be limited.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Several studies on TYMS expression and this polymorphism were reported especially in colorectal cancer, with some clinical studies showing favorable results in 2R/2R (32)(33)(34). However, two recent studies in advanced gastric cancer did not show any significant impact of this polymorphism as seen with our results (7,9). Although further studies may be necessary, the clinical significance of this polymorphism may be limited.…”
Section: Discussioncontrasting
confidence: 47%
“…5,10-Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in folate metabolism, which catalyzes the irreversible conversion of 5-10-methylene tetrahydrofolate to 5-methyltetrahydrofolate (5). Because decreased activity of MTHFR may result in accumulation of 5-10-methylene tetrahydrofolate and improve the antitumor efficacy of FU, several studies evaluated genetic polymorphisms of MTHFR, with or without genetic polymorphisms of TYMS in patients with advanced gastric cancer, although the clinical data are still controversial (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…An essential member of the NER pathway is XPD, which is a key rate-limiting enzyme in NER and works as an ATP-e. Previous studies have indicated that the XPD Lys751Gln polymorphism is associated with suboptimal DRC and determined the effects on clinical outcomes of oxaliplatinbased regimens in CRC (Park et al, 2001;Stoehlmacher et al, 2004), esophageal cancer (Leichman et al, 2011) and gastric cancer (Keam et al, 2008). Therefore, the functional XPD Lys751Gln polymorphism may reveal the mechanism to resistance to oxaliplatin and serve as a useful predictive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies on lung cancer [10] and colorectal cancer [9,11,20,21] showed opposite results. In addition, several studies demonstrated that no clear association was found between ERCC1 codon 118 polymorphism and platinum sensitivity [24][25][26] . In a recent study on advanced gastric cancer treated with fluorouracil/cisplatin palliative chemotherapy, a tendency to higher response rate was found in patients with C allele (P = 0.09).…”
Section: Discussionmentioning
confidence: 99%